Attenuation From Shoes and Pads in Equine Nuclear Scintigraphy, With Relevance to Solar Views - Walker, Lea; Martinelli, Mark J.; Rantanen, Norman; Drumond, Bianca; Trostle, Steven (Frontiers in Veterinary Science, 2020)
Nuclear scintigraphy can be beneficial in the investigation of equine lameness and poor performance. Images obtained through the sole allow for better identification of a region of increased radionuclide uptake in the foot. The presence of shoes or pads may affect these images. To determine the degree of radioactive attenuation different types of shoes and pads of different thickness and materials were evaluated by placing the material directly on the gamma camera detector acquiring flood images from a point source. The study compared five different types of shoes from 3 different shoeing materials, steel, aluminum, and polyurethane. This study also assessed 8 different types of pads that were selected based on the subjective densities and variable rigidity of the materials. All types of shoes/pads evaluated caused some degree of attenuation (P < 0.05). Steel shoes of all types cause the most attenuation (54%), followed by aluminum shoes (22%), and the shoes or pads composed primarily of a plastic polymer cause the least amount of attenuation (15%). The results of the study found that pads or shoes cause significant (p<0.05) attenuation of gamma radiation. Composition, thickness and density characterized mass absorption coefficient, of the material affect the amount of gamma radiation attenuation. Because of the attenuation of gamma radiation, we recommend shoes and pads be removed prior to nuclear scintigraphic examination of the front foot if a solar image is desired, as this attenuation may affect image quality.